Use of data on planned contributions and stated beliefs in the measurement of social preferences - Anna Conte; M. Vittoria Levati (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
In a series of one-shot linear public goods game, we ask subjects to report their contributions, their contribution plans for the next period, and their first-order beliefs about their present and future partner. We estimate subjects' preferences from plans data by a infinite mixture approach and compare the results with those obtained from contribution data. Our results indicate that preferences are heterogeneous, and that most subjects exhibit conditionally cooperative inclinations. Controlling for beliefs, which incorporate the information about the other's decisions, we are able to show that plans convey accurate information about subjects' preferences and, consequently, are good predictors of their future behavior.
Keywords: C35; C51; C72; H41; 330; public goods games; experiments; social preferences; mixture models; Öffentliches Gut; Spieltheorie; Soziale Wohlfahrtsfunktion; Messung; Test